PMO-212 Patients with positive faecal occult blood test (FOBt) following previous low risk colonoscopy in the bowel cancer screening programme: should current approach be changed?. (28th May 2012) - Nylander, D; Ritchie, M
Abstract : Introduction: In the UK FOBt Bowel Cancer Screening Programme (BCSP), patients between 60 and 75 are invited to submit stool specimens 2 yearly. Those who have either two weakly positive (+ve) or one abnormal FOBt are recommended to undergo colonoscopy. This recommendation stands, even if they have had a previous colonoscopy within the BCSP, regardless of the findings or time frame. In theory therefore a patient may be recommended colonoscopy every 2 years if they have any persisting non-neoplastic lesions that cause bleeding. BSG guidance however recommends surveillance colonoscopy in 5 years (or not at all) for patients with low risk adenoma. 1 All endoscopists in BCSP have been assessed and deemed competent colonoscopists. Also all procedures are carefully monitored by specialist practitioners. Thus this is the most quality assured setting for colonoscopy practice in the health service. We aimed (a) To determine if there were patients who returned to for 2nd BCSP colonoscopy in under 5 years, despite previous colonoscopy being classed as low risk or non-neoplastic. (b) To determine if 2nd colonoscopy gave prognostically significant result. Methods: The BCSP database was used to identify cases with 1st colonoscopy reported as normal, low risk adenomas or "abnormal but no adenoma". Any of these who had a 2nd colonoscopy within the BCSP for +ve FOBt were noted and their reports obtained to get the findings of both procedures. The study period was April 2007 to October 2011. Results: 40 patients, deemed low risk at 1st BCSP colonoscopy returned new positive FOBt kits in following screening round. Of these two declined 2nd colonoscopy when contacted (initial colonoscopy findings were one Crohns, one diverticulosis). In three cases, interval between colonoscopies was 4 years, all the rest being 2 years. All colonoscopy findings are in Abstract PMO-212 table 1 . All adenomas were 3 mm or less. Conclusion: A small number of patients will have positive FOBt tests despite a "low risk" colonoscopy in BCSP for neoplasia within previous 2 years. In our patient group, a 2nd colonoscopy in this period showed no new prognostically significant findings. Our data suggests that there is no need to deviate from the BSG recommendation and perform repeat procedures for "low risk" patients in <5 years in the BCSP. Competing interests: None declared. Reference: 1. Gut 2010;59 :666.